Adoecer por TB/HIV: os efeitos de sentido a partir da perspectiva discursiva de indivíduos coinfectados em um município do interior do Estado de São Paulo - Reis, Amanda Alessandra dos (2016)
This is a qualitative based study, supported by methodological theoretical framework Speech Analysis of French Matrix, which seeks to understand these production processesin the relation of langua get o the historical and social externality of the subject. The study aimed to analyze the senses produced by the disease processin patients with TB/HIV. This proposal was developed with patients using the Care Center of Chronicle Infections of a city in the São Paulo state. The data collection was divided into two stages :the first stage was collected by the multi-professional team, through the Book of Registration and Monitoring of Tuberculosis Cases Treatment, the National Disease Reporting Information System(Sinan), TBWEB and socio demographic data in order to characterize the subjects of this investigation. In the second stage individual interviews were conductedwith06TB /HIV co-infected patients; the interviews were semi-structured and audio-recorded. The transcriptions were organized with ATLAS.ti7software feature, which facilitated the organization of empirical data. The results of this research demonstrate that some subject sin the interview and patient position assume a standard circulating conception in society, in which HIV is inextricably linked torisky behaviors (drug use and unprotected sex) that propitiate infection by this virus. In addition, was possible to observet he importance of the link between the patient and the health professional in strengthening and continuity of treatment. Considering the above, there is the need to strengthen the recommendations by the Health Ministry about the co-infection TB /HIV using health strategies or actions not only to patients and health professionals, but also t of families and care givers of these patients.